ÉTICA: QUESTÕES E PROBLEMAS CONTEMPORÂNEOS - Bonilla, Alcira B. (2016)
Moral philosophy or ethics holds nowadays the rank of “First Philosophy”. In this article I try to reflect the state of art in this field. The text is divided in four sections: “Clearing the language: moral and ethics”, “The phenomenon of the morality”, “The technical use of the words by current thinkers”, and “’Applied Ethics’ and the contemporary ‘Ethical turn’”.